Dynamic Interactions Between Financial and Macroeconomic Imbalances: A Panel VAR Analysis - Amat Adarov (The Vienna Institute for International Economic Studies (wiiw), 2019)
We use Bayesian and GMM panel VAR frameworks to study interactions between financial cycles and macroeconomic imbalances based on a global sample of 24 countries spanning the period 1998‑2012. We find that financial cycles play an important role in shaping macroeconomic imbalances with expansions inducing economic overheating and a downward pressure on public debt-to-GDP ratios, and vice versa. Bank-based economies exhibit a deeper and faster response of business cycles to financial misalignments, while the impact in market-based economies is milder, but more persistent, as well as more significant for current account and public debt dynamics. Financial cycles invoke a particularly strong reaction of current account balances and especially public debt ratios in the euro area.
Keywords: E44; F32; G15; F4; 330; financial cycles; macroeconomic imbalances; financial stability; business cycles; panel VAR; Bayesian VAR